2017
DOI: 10.3390/nu9060609
|View full text |Cite
|
Sign up to set email alerts
|

Protein Hydrolysates as Promoters of Non-Haem Iron Absorption

Abstract: Iron (Fe) is an essential micronutrient for human growth and health. Organic iron is an excellent iron supplement due to its bioavailability. Both amino acids and peptides improve iron bioavailability and absorption and are therefore valuable components of iron supplements. This review focuses on protein hydrolysates as potential promoters of iron absorption. The ability of protein hydrolysates to chelate iron is thought to be a key attribute for the promotion of iron absorption. Iron-chelatable protein hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 110 publications
0
45
0
1
Order By: Relevance
“…The stomach does not contribute much in the assimilation of iron, as its absorption is ≤2% of the total intake (15). There are two types of dietary iron that may be absorbed: Heme iron, from the breakdown of hemoglobin and myoglobin in red meat, or non-heme inorganic iron, which is predominantly released from foods, including vegetables and cereals (16,17).…”
Section: Iron Absorptionmentioning
confidence: 99%
“…The stomach does not contribute much in the assimilation of iron, as its absorption is ≤2% of the total intake (15). There are two types of dietary iron that may be absorbed: Heme iron, from the breakdown of hemoglobin and myoglobin in red meat, or non-heme inorganic iron, which is predominantly released from foods, including vegetables and cereals (16,17).…”
Section: Iron Absorptionmentioning
confidence: 99%
“…In particular, specific casein hydrolysates from bovine milk demonstrate antioxidant activity via radical scavenging properties in both aqueous and lipid model systems [8][9][10][11][12][13]. Casein phosphopeptides (CPPs) derived from tryptic digests of casein also have a strong affinity to sequester divalent metal ions, such as non-heme iron and copper, two potential food pro-oxidants under specific conditions [14][15][16]. Bovine milk casein-derived CPPs may therefore serve to remove pro-oxidative metal catalysts such as iron from an environment of oxidizable lipids to prevent lipid oxidation [17].…”
Section: Introductionmentioning
confidence: 99%
“…heme iron and copper, two potential food pro-oxidants under specific conditions [14][15][16]. Bovine milk casein-derived CPPs may therefore serve to remove pro-oxidative metal catalysts such as iron from an environment of oxidizable lipids to prevent lipid oxidation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that Fe chelate complexes can promote the absorption of Fe. [5][6][7][8][9] At the same time, Fe in the form of a stable chelate complex is less harmful to tissues as it does not produce ROS.…”
Section: Introductionmentioning
confidence: 99%